The thesan project: properties of the intergalactic medium and its connection to reionization-era galaxies. Issue 4 (14th February 2022) - Garaldi, E; Kannan, R; Smith, A; Springel, V; Pakmor, R; Vogelsberger, M; Hernquist, L
ABSTRACT: The high-redshift intergalactic medium (IGM) and the primeval galaxy population are rapidly becoming the new frontier of extragalactic astronomy. We investigate the IGM properties and their connection to galaxies at z ≥ 5.5 under different assumptions for the ionizing photon escape and the nature of dark matter, employing our novel thesan radiation-hydrodynamical simulation suite, designed to provide a comprehensive picture of the emergence of galaxies in a full reionization context. Our simulations have realistic 'late' reionization histories, match available constraints on global IGM properties, and reproduce the recently observed rapid evolution of the mean free path of ionizing photons. We additionally examine high- z Lyman-α transmission. The optical depth evolution is consistent with data, and its distribution suggests an even-later reionization than simulated, although with a strong sensitivity to the source model. We show that the effects of these two unknowns can be disentangled by characterizing the spectral shape and separation of Lyman-α transmission regions, opening up the possibility to observationally constrain both. For the first time in simulations, thesan reproduces the modulation of the Lyman-α flux as a function of galaxy distance, demonstrating the power of coupling a realistic galaxy formation model with proper radiation hydrodynamics. We find this feature to be extremely sensitive on the timing of reionization, while being relatively insensitive to the source model. Overall, thesan produces a realistic IGM and galaxy population, providing a robust framework for future analysis of the high- z Universe.